Twelve-month prevalence and disability of DSM-IV bipolar disorder in an Australian general population survey - MITCHELL, P. B.; SLADE, T.; ANDREWS, G. (Psychological medicine, 2004)
Background. There have been few large-scale epidemiological studies which have examined the prevalence of bipolar disorder. The authors report 12-month prevalence data for DSM-IV bipolar disorder from the Australian National Survey of Mental Health and Well-Being. Method. The broad methodology of the Australian National Survey has been described previously. Ten thousand, six hundred and forty-one people participated. The 12-month prevalence of euphoric bipolar disorder (I and II) – similar to the euphoric-grandiose syndrome of Kessler and co-workers – was determined. Those so identified were compared with subjects with major depressive disorder and the rest of the sample, on rates of co-morbidity with anxiety and substance use disorders as well as demographic features and measures of disability and service utilization. Polychotomous logistic regression was used to study the relationship between the three samples and these dependent variables. Results. There was a 12-month prevalence of 0·5% for bipolar disorder. Compared with subjects with major depressive disorder, those with bipolar disorder were distinguished by a more equal gender ratio; a greater likelihood of being widowed, separated or divorced; higher rates of drug abuse or dependence; greater disability as measured by days out of role; increased rates of treatment with medicines; and higher lifetime rates of suicide attempts. Conclusions. This large national survey highlights the marked functional impairment caused by bipolar disorder, even when compared with major depressive disorder.